A comparative surface analysis of explanted hip prostheses: stainless steel and Co-Cr alloy versus titanium alloy (2021)
ABSTRACT : The introduction of modular design in total hip arthroplasty has enabled the use of different materials in one single configuration and the adjustment of the prosthesis to the patient’s body, and facilitated medical revisions. However, modularity leads to the presence of new interfaces created between pieces in contact, raising the issue of degradation. Tribocorrosion phenomena have been identified as the main degradation mechanism due to the mechanical, chemical, and electrochemical conditions acting on the materials. In addition, conditions inside the human body are unclear, regarding electrochemical settings and the interaction between the electrochemical and mechanical action. This work is focused on the degradation of monopolar hip joint implants made from biomedical alloys such as stainless steel, Ti, and CoCr alloys. Three cases are presented and analyzed in terms of the degradation level along the trunnion length. Surface analysis done on a titanium trunnion showed a significant ploughing on the distal part, compared to what was found for stainless steel and cobalt-chromium alloys, which can produce a stuck in this area. Meanwhile, in the proximal part, wear debris is found, which suggests more movement in the internal part. Although few debris particles were identified in CoCr trunnion, a large amount of material inside the contact was observed. This could be related to the ploughing generated in the distal thread pattern, which allowed the material to come inside and outside the contact.